Beau geste, with ebook eaudiobook - Wren, Percival (Tantor Media, 2009)
A column of French Legionnaires finds one of their fortresses manned by dead men. It looks like the sergeant was killed by one of his own troops. Who could have done it? A flashback then unravels the mystery of the three English Geste brothers. The brothers, orphaned early in life, are raised by an aunt. Their raucous youths are filled with the literature of adventure and ritualized horseplay centered around these myths and legends. So when the family's prized Blue Water sapphire turns up missing, each of the young men confesses to being the thief in order to protect the others, and one by one they head off to join the French Foreign Legion. The three brothers meet up in the deserts of Africa, where they fall under the command of the malevolent Sergeant Lejaune. Not content to merely be a martinet, Lejaune sets his sights on stealing the jewel, which rumor holds to be in the brothers' possession. Meanwhile, the unruly troops he commands are planning a mutiny, and the marauding Tauregs pin this badly outnumbered and bitterly divided unit of Legionnaires at Fort Zinderneuf. The ensuing drama plays itself out as the French forces battle overwhelming odds. Ultimately, only a handful of men survive to discover the truth behind the Blue Water's disappearance. A classic, rip-roaring tale of adventure!